Synthesis and NMR characterization of SAPO-35 from non-aqueous systems using hexamethyleneimine template - Venkatathri, N (Materials Research Bulletin, 2005)
SAPO-35 was synthesized using hexamethyleneimine template in non-aqueous systems. X-ray diffraction and scanning electron micrograph analysis shows the synthesized sample is pure and well crystalline. Presence of four stages (1.6%, 0.8%, 7.8% and 8.4%) of weight loss is observed by TG/DTA analysis. FT-IR analysis in the framework region shows the presence of tetrahedral T-O-T vibrations is similar to the other known aluminophosphate molecular sieves. FT-IR spectrum in the -OH region shows stretching vibrations at 3631, 3604 and 3580 cm(-1) can be assigned to OH groups in bigger cages near S6R, in bigger cages near D6R and those actually confined inside the D6R, respectively. The spectra for the as-synthesized sample show a single symmetrical Al-27 MAS NMR line at delta = 36.26 indicating the presence of a single tetrahedral aluminium species. Where as Si-29 and P-31 MAS NMR shows the presence of two peaks in both at (-89.9 and -95.15 ppm) and (-34.01 and -40.45 ppm) due to the Si substitution of P present in two different locations in double 6 ring (D6R) and in single 6 ring (S6R). Al-27 3Q-MAS NMR shows two peaks for environmentally different tetrahedral aluminium atoms. This is the first time we are showing such a fact which is not observable using ordinary MAS NMR. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: XRD